The industrial potentialities of Northern Nigeria (Kaduna : Ministry of Trade and Industry, 1963)
The subject matter is based upon an industrial and economic survey of Northern Nigeria undertaken by these two organizations and sponsored by the Government of Northern Nigeria and the United Kingdom Department of Technical Co-operation.
Includes bibliographical references.
hza 01/02/2019
Loans
Keywords: Industries; Nigeria, Northern